Show that the Quotient Rule of Logarithms works for the base 4 expression log^4 64−log^4 16 .

1 answer

To demonstrate that the Quotient Rule of Logarithms holds for the expression \( \log_4 64 - \log_4 16 \), we can use the Quotient Rule itself, which states:

\[ \log_b \frac{a}{c} = \log_b a - \log_b c \]

This means that the left-hand side is equivalent to taking the logarithm of the quotient of \( a \) and \( c \).

Let's first calculate \( \log_4 64 - \log_4 16 \):

  1. Calculate \( \log_4 64 \): We express 64 as a power of 4: \[ 64 = 4^3 \] Thus, \[ \log_4 64 = \log_4 (4^3) = 3 \]

  2. Calculate \( \log_4 16 \): We express 16 as a power of 4: \[ 16 = 4^2 \] Thus, \[ \log_4 16 = \log_4 (4^2) = 2 \]

Now, we can substitute these values into our original expression:

\[ \log_4 64 - \log_4 16 = 3 - 2 = 1 \]

  1. Calculate \( \log_4 \frac{64}{16} \): Now, according to the Quotient Rule, we can compute: \[ \frac{64}{16} = 4 \] Thus, \[ \log_4 \frac{64}{16} = \log_4 4 \] Since \( 4 = 4^1 \), we have: \[ \log_4 4 = 1 \]

Finally, we have shown that:

\[ \log_4 64 - \log_4 16 = 1 \]

and using the Quotient Rule we found:

\[ \log_4 \frac{64}{16} = 1 \]

Thus, we conclude that:

\[ \log_4 64 - \log_4 16 = \log_4 \frac{64}{16} \]

This verifies that the Quotient Rule of Logarithms indeed works for the expression \( \log_4 64 - \log_4 16 \). Therefore, the claim is proven.